Feeling of alienation and social support in case of juveniles - Biegasiewicz, Monika (Studia Psychologica: Theoria et praxis, 2010)
The objective of this article is the analysis of relation between the feeling of alienation and social support of juveniles as factors that may occur and affect the criminal behaviour. The research applied the Scalę of feeling of alienation and the Scalę of Social Support by author K. Kmiecik-Baran. The group of 107juveniles residing in thejuvenile Shelter and young offenders’ institution has been researched. There was a hypothesis of negative correlation between feeling of alienation and social support. It was assumed that the strength of hond between the feeling of alienation and feeling of social support depends on the source of help and support and that young people are provided with support such as IT support, tools usage, emotional mainly by peers and with less impact of parents. The research confirms majority of given hypothesis.The results shows the strongest connection between getting a support from parents and feeling of social integration ofjuveniles, at the same time parents in connection with other people (further relatives and strangers such as neighbours, colleagues from the housing estate) provide the juveniles with relatively slightly support. The performed researched confirm the role of widely understood childcare neglect by the family environment on the way to delinąuency and feeling of alienation and lack of social support as variables in his process Poczucie alienacji a wsparcie społeczne u nieletnich